2014
DOI: 10.1016/j.lungcan.2014.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of galectin-1 expression in non-small cell lung cancer patients

Abstract: We conclude that Gal-1 expression may be a useful biomarker for better prediction of the clinical outcome and management of NSCLC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 30 publications
2
26
0
2
Order By: Relevance
“…Kim et al 11 showed that Gal-1 significantly induced cell proliferation and invasion in epithelial ovarian cancer cells. In various tumours, Gal-1 overexpression has been shown to be associated with poor prognosis,11 30 31 tumour invasiveness17 19 and tumour grade 32. In recent years, the clinicopathological significance of Gal-1 expression in head and neck SCC (HNSCC) has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 11 showed that Gal-1 significantly induced cell proliferation and invasion in epithelial ovarian cancer cells. In various tumours, Gal-1 overexpression has been shown to be associated with poor prognosis,11 30 31 tumour invasiveness17 19 and tumour grade 32. In recent years, the clinicopathological significance of Gal-1 expression in head and neck SCC (HNSCC) has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…54,55 Carlini et al proposed that galectin-1 may be used as a potential biomarker to better predict the clinical outcome and management of NSCLC patients. 56 Since the aforementioned works were performed in cell lines and tumor tissues, the decreased level of galectin-1 in blood from early stage patients (stages I and II) may result from its intracellular accumulation, which could contribute to promoting tumor growth. The lower expression level in blood has been verified by ELISA here, and the mechanism and potential application await elucidation by further studies.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Гелзолин, выполняющий функцию актин-связывающего белка, ранее уже рассматривался в качестве кандидатного маркера для многих типов опухолей, в том числе рака молочной железы, толстой кишки, предстательной железы, мочевого пузыря и рака лёгких [84][85][86][87][88]. Галектин 1, участвующий в регуляции апоптоза, пролиферации и дифференцировки клеток, в случае АКЛ задействован в миграции клеток, инвазии и опухолевой прогрессии [89,90]. Цитоплазматический актин 1 участвует во множестве процессов, связанных с подвижностью клеток, его экспрессия была повышена у пациентов на всех стадиях АКЛ по сравнению со здоровым контролем [39].…”
Section: направленный масс-спектрометрический анализunclassified